The role of ultrasound and genetic counsel in prenatal diagnosis of split hand/foot malformation with long bone deficiency - Anna Kucińska-Chahwan; Dominika Szczęśniak; Beata Nowakowska; Tomasz Roszkowski (Elsevier, 2019)
Objective: The aim of the report is to highlight importance of careful ultrasound examination and genetic counsel in case of split hand/foot prenatal diagnosis. Evaluation of the accompanying long bone deficiency indicates that array comparative genomic hybridization (aCGH) should be used. Case report: We present a prenatal diagnosis of split hand/foot malformation with long bone deficiency type 3 (SHFLD3) in a patient suffering from congenital limb anomalies but without previous molecular diagnosis. Genetic consultation and prenatal testing were offered. While karyotype was normal, aCGH revealed microduplication in locus 17p33.3. Microarray analysis was carried out also in pregnant patient and her asymptomatic mother and gave positive results on both. Conclusion: Prenatal diagnosis of SHFLD3 either imaging or cytogenetic is possible. Both methods should be used to make a correct diagnosis. Due to reduced penetrance of SHFLD3 not all individuals carrying microduplication present clinical findings. Therefore, pedigree analysis and genetic counsel is important for whole family and not only for affected members. Advances in genetics may allow to establish exact diagnosis in previously undiagnosed patients. Keywords: Ectrodactyly, Genetic counsel, Microduplication, Split hand/foot, Tibial aplasia